Spatio-temporal aware privacy-preserving scheme in LBS - Weihao LI; Sheng DING; Jiajie MENG; Hui LI (Tongxin xuebao)
Location-based service (LBS) brings a lot of conveniences in people’s daily life,but the conveniences are accompanied with the leaking of privacy.A dummy-based location-preserving scheme was proposed,which took the correlation between spatial issues and temporal issues into account.Two algorithms were included in this scheme,map dividing algorithm and dummy contents determining algorithm.The map dividing algorithm divided the map into discrete location cells by Voronoi Diagram to ensure these discrete location cells were not adjacent to each other.The dummy contents determining algorithm replaced the query content in previous moment by the intending location in next moment,which efficiently avoided the adversary inferring mobile users’ sensitive information according to the correlation between spatial issues and temporal issues.The simulation experiments show that the proposed scheme is effective and efficient.